1984
DOI: 10.1099/00221287-130-1-167
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Gas Vesicles from Methanosarcina barken

Abstract: A gas-vacuolate strain of Methanosarcina barkeri formed protoplasts in substrate-depleted cultures and gas vesicles were isolated from the protoplasts. Vacuolate protoplasts were separated from unvacuolate ones by flotation and the protoplast membrane was removed by Tween 20, liberating the gas vesicles. The gas vesicles were purified by flotation after initial passage through a 0.45 pm filter to remove contaminating material. Gas vesicle membranes were purified by isopycnic gradient centrifugation and were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The sequence adjacent to the 5Ј end includes the same order of gene orthologs found in Among genes encoding biosynthetic functions, a group of 14 sequential ORFs encode predicted gas vesicles with highest identity to gvpANOFGJKLM (MbarA 326 to 339) in the haloarchaea, which includes the minimal gene set for expression of vesicle in Haloferax volcanii (34). Although there are no prior reports of gas vesicles in M. barkeri Fusaro, gas vesicles have been reported in another strain of M. barkeri, FR-1, and in Methanosarcina vacuolata, which has a DNA-DNA reassociation value of 61% with the type strain of M. barkeri (1,51,52). Interestingly, M. barkeri has three sequential copies of gvpA that encode the ribs of the vesicle wall and influence the strength and width of the vesicles (4).…”
Section: Resultsmentioning
confidence: 96%
“…The sequence adjacent to the 5Ј end includes the same order of gene orthologs found in Among genes encoding biosynthetic functions, a group of 14 sequential ORFs encode predicted gas vesicles with highest identity to gvpANOFGJKLM (MbarA 326 to 339) in the haloarchaea, which includes the minimal gene set for expression of vesicle in Haloferax volcanii (34). Although there are no prior reports of gas vesicles in M. barkeri Fusaro, gas vesicles have been reported in another strain of M. barkeri, FR-1, and in Methanosarcina vacuolata, which has a DNA-DNA reassociation value of 61% with the type strain of M. barkeri (1,51,52). Interestingly, M. barkeri has three sequential copies of gvpA that encode the ribs of the vesicle wall and influence the strength and width of the vesicles (4).…”
Section: Resultsmentioning
confidence: 96%
“…The primary role of buoyancy in phototrophs is to maintain the micro-organisms either near the surface of the water or in the metalimnion of lakes, where they are exposed to favourable light intensities (Walsby, 1994). In other gas-vacuolate micro-organisms, such as the methanogen Methanosarcina barkeri (Archer & King, 1984) and various sea-ice bacteria (Gosink & Staley,199S), the role of buoyancy is less obvious. Petter (1932) suggested that gas vesicles might be important to aerobic halobacteria in buoying them to the water surface, where the concentrations of oxygen are highest.…”
Section: Introductionmentioning
confidence: 99%
“…To isolate gas vesicles, cells are allowed to grow in substrate depleted medium which results in the formation of protoplast (Archer and King, 1984).Vacuolate protoplasts are separated from unvacuolate ones by flotation and the protoplast membrane removed by Tween 20, liberating the gas vesicles. The gas vesicles are then purified by flotation after initial passage through a 0.45 pm filter to remove contaminating material.…”
Section: Gas Vesiclementioning
confidence: 99%